Cardiac point-of-care ultrasound in hospitalized coronavirus disease-2019 patients: findings and association with outcome. Issue 1 (January 2022) - Gilad, Vered; De Marzo, Vincenzo; Guglielmi, Giulia; Bona, Roberta Della; Giovinazzo, Stefano; Pescetelli, Fabio; Valbusa, Alberto; Bezante, Gian Paolo; De Maria, Andrea; Patroniti, Nicolò; Ferone, Diego; Pelosi, Paolo; et al.
Abstract : Supplemental Digital Content is available in the text